2009
DOI: 10.1016/j.jvolgeores.2009.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Geodynamics of the Yellowstone hotspot and mantle plume: Seismic and GPS imaging, kinematics, and mantle flow

Abstract: The Yellowstone hotspot resulted from interaction of a mantle plume with the overriding North America plate highly modifying the lithosphere by magmatic-tectonic processes and producing the 17 Ma Yellowstone-Snake River Plain (YSRP) volcanic system. The accessibility of the YSRP has allowed largescale geophysical experiments to seismically image the hotspot and to evaluate its kinematic and dynamic properties using geodetic measurements. Tomography reveals a Yellowstone crustal magma body with 8-15% melt that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
168
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(187 citation statements)
references
References 185 publications
12
168
0
Order By: Relevance
“…Assuming the mantle plume is the dominant heat source and perfectly transfers the heat into the lowermost crust, we can then use the excess temperature of the plume to assess the velocity reduction in the lower crust. Previous studies have suggested the excess temperature of the Yellowstone plume to be 55-120 K (2,46). Using this value together with the temperature coefficient of mafic granulite gives a VP decrease of 0.029-0.062 km/s, corresponding to a 0.4-0.9% velocity reduction.…”
Section: Velocity Anomalies Caused By Temperaturementioning
confidence: 94%
“…Assuming the mantle plume is the dominant heat source and perfectly transfers the heat into the lowermost crust, we can then use the excess temperature of the plume to assess the velocity reduction in the lower crust. Previous studies have suggested the excess temperature of the Yellowstone plume to be 55-120 K (2,46). Using this value together with the temperature coefficient of mafic granulite gives a VP decrease of 0.029-0.062 km/s, corresponding to a 0.4-0.9% velocity reduction.…”
Section: Velocity Anomalies Caused By Temperaturementioning
confidence: 94%
“…The Snake River Plain (SRP) of central Idaho is a manifestation of Yellowstone-Snake River Plain (YSRP) hotspot volcanism and contains intriguing evidence for mantle hotspot impingement on continental crust (Pierce and Morgan, 1992;Hanan et al, 2008;Shervais and Hanan, 2008;Smith et al, 2009;Jean et al, 2014). The region contains a record of continuous bimodal volcanism extending over 17 Ma Coble and Mahood, 2012;Henry et al, 2017) to the present, and documents the migration of timetransgressive rhyolitic volcanism from the Bruneau-Jarbidge volcanic center (circa 12 Ma) to its present location beneath the Yellowstone Plateau (Pierce and Morgan, 1992;Anders et al, 2009).…”
Section: Introductionmentioning
confidence: 93%
“…The eastern Hot Spring Basin hydrothermal system includes a hydrothermal explosion crater, some hydrothermal pools, a small pond and the uppermost reaches of Wrong Creek. A low-velocity, upper-mantle body or plume is the conduit for an ascending melt associated with the Yellowstone hotspot [16]. The plume's buoyancy produces a ~400-km wide and ~500 m topographic high centered on the Yellowstone Plateau.…”
Section: Geographic and Geologic Settingmentioning
confidence: 99%